Effects of Nuclear Genomes on Anther Development in Cytoplasmic Male Sterile Chicories (Cichorium intybus L.): Morphological Analysis - Ildephonse Habarugira; Theo Hendriks; Marie-Christine Quillet; Jean-Louis Hilbert; Caroline Rambaud (The Scientific World Journal)
The Cichorium intybus flower development in fertile, cytoplasmic male sterility (CMS 524) and various phenotypes carrying the 524 male sterile cytoplasm was investigated macroscopically and by light microscopy. The development was similar in fertile and in male sterile florets up to meiosis, and then it was affected in anther wall structure and pollen grain development in male sterile floret. In the male sterile plants, the tapetum intrusion after meiosis was less remarkable, the microspores started to abort at vacuolate stage, the connective tissue collapsed, and endothecium failed to expand normally and did not undergo cell wall lignification, which prevented anther opening since the septum and stomium were not disrupted. Crosses undertaken in order to introduce the CMS 524 into two different nuclear backgrounds gave rise to morphologically diversified progenies due to different nuclear-mitochondrial interactions. Macroscopic and cytological investigations showed that pollen-donor plants belonging to Jupiter population had potential capacity to restore fertility while the CC line could be considered as a sterility maintainer.